Nitrogen dioxide detection using copper oxide thin film sensor prepared by direct current sputtering technique - Mohd. Sukri, Nurul Ain (2014)
Semiconducting copper oxide (CuO) thin films have been deposited using DC sputtering technique using copper (Cu) target for detection of oxidizing nitrogen dioxide (NO2) gas. A series of CuO thin films (gas sensors) (C1-C7) of various thicknesses had been prepared on Corning glass substrate. The time of deposition was between 90 to 270 minutes at 30-minutes time interval. The thickness of the gas sensors was measured using a surface profiler (Dektak 3) and found to be in the range between 159 nm to 604 nm. The resistance and the gas sensing properties to NO2, mainly the sensitivity, response and recovery time were investigated using the gas sensor characterization system (GSCS) for a single gas sensor and for an array of sensors in series configurations at different operating temperatures. The resistance of the gas sensor decreased when exposed to NO2 gas. The best sensitivity (0.859) for the single gas sensor configuration was found to be sensor C3 which was deposited at 150 minutes, corresponding to 247 nm thickness. While, for the sensor array configuration, the best sensitivity (0.788) was found to be sensor AC3 at the combination of 90 and 150 minutes-deposition time. The response time for the gas sensor C3 was 57 seconds and the recovery time was 60 seconds; whereas for the array gas sensor AC3, the response and recovery time were 45 seconds and 60 seconds, respectively. Thus, the single configuration had a better sensitivity and response time compared to the array configuration. Hence, the single configuration was the preferable gas sensor for NO2 gas.